Complete Genome Sequence of Bacillus subtilis BAB-1, a Biocontrol Agent for Suppression of Tomato Gray Mold - Guo, Qinggang (American Society for Microbiology, 2014)
Bacillus subtilis BAB-1, isolated from cotton rhizosphere soil, is an excellent biocontrol agent for tomato gray mold. The genome of B. subtilis strain BAB-1 was fully sequenced and annotated, genes encoding the antifungal active compound were identified, and multiple sets of regulatory systems were found in the genome.